ANALISIS PELAKSANAAN PENETAPAN ASAL USUL ANAK SEBAGAI UPAYA PERLINDUNGAN HUKUM TERHADAP ANAK DARI PERKAWINAN SIRI PADA PENGADILAN AGAMA KUPANG - Musdalifah, Musdalifah; Ndolu, Juliana Susantje; Dinata, Husni Kusuma (Petitum Law Journal, 2025)
Determination of the origin of children from unregistered relationships at the Kupang Religious Court is an important step to ensure the identity, inheritance, and maintenance rights of children born from unregistered marriages. This study investigated the determination process by interviewing judges, court clerks, and six applicants, and analyzing secondary data. The findings show that the determination hearing process is carried out in two stages: identity verification and proof of unregistered marriage through witnesses, ending with the determination of the child's status as legitimate and biological. All respondents (100%) thought that the process was smooth, transparent, and affordable. However, there were several obstacles, including low public understanding of the determination procedure, lack of official marriage evidence (which requires isbat nikah), and difficulty in presenting valid witnesses due to the time gap since the unregistered marriage took place. Low participation in the socialization of the mobile court also worsened the situation. This study recommends collaboration between the court and the government in providing legal education, simplifying administration, and strengthening legal aid services (posbakum) to increase access. Thus, although the determination process is in accordance with the principles of justice, the protection of children from unregistered relationships still requires a comprehensive approach that focuses on legal literacy and cooperation between institutions.